2020
DOI: 10.3390/molecules25184087
|View full text |Cite
|
Sign up to set email alerts
|

NOx-Reduction Performance Test for TiO2 Paint

Abstract: In South Korea, the gradual increase in particulate matter generation has received significant attention from central and local governments. Exhaust gas, which contains nitrogen oxides (NOx), is one of the main sources of particulate matter. In this study, the reduction of NOx using a coating material mixed with a titanium dioxide (TiO2) photocatalyst was demonstrated. The NOx reduction performance of the TiO2 photocatalyst-infused coating was evaluated by applying the ISO 22197-1 2007 standard. Subsequently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In addition, they determined that the rate of NO removal was reduced when the photocatalytic cementitious material was rewetted. Song et al [28] studied the NOx removal performance of TiO 2 -based coating materials used as paint. They demonstrated that sufficient NOx removal can be achieved although the NO gas concentration and UV-A irradiance are smaller than the experimental conditions of the ISO 22197-1: 2007 standard when their TiO 2 photocatalyst-infused coating is used.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they determined that the rate of NO removal was reduced when the photocatalytic cementitious material was rewetted. Song et al [28] studied the NOx removal performance of TiO 2 -based coating materials used as paint. They demonstrated that sufficient NOx removal can be achieved although the NO gas concentration and UV-A irradiance are smaller than the experimental conditions of the ISO 22197-1: 2007 standard when their TiO 2 photocatalyst-infused coating is used.…”
Section: Introductionmentioning
confidence: 99%